Influences of professional self-concept and job stress of nurses working in Korea dementia care centers on turnover intention - Kim, Mi Young; Gu, Minkyung; Oh, Nam Kyung; Sok, Sohyune (Frontiers in Public Health, 2025)
BackgroundAs the older adult population increases, the prevalence of dementia is increasing. The number of nurses working in dementia care centers is increasing, and related research is needed for them.ObjectiveThis study aimed to examine the influences among professional self-concept, job stress, and turnover intention, and the factors influencing turnover intention of nurses working at dementia care centers.MethodsA cross-sectional explanatory survey with path analysis was employed. Participants were 160 nurses working in dementia care centers in South Korea. Measures were the general characteristics list, the Professional Self-Concept of Nurses Instrument, the job stress scale, and turnover intention measurement instrument.ResultsTurnover intention was positively correlated with job stress (r = 0.35, p < 0.01), and it was negatively correlated with professional self-concept (r = −0.42, p < 0.01). The job stress (β = 0.53, p < 0.001), age (β = −0.22, p = 0.048), educational level (β = 0.19, p = 0.014), and professional self-concept (β = −0.19, p = 0.023) were statistically significant factors influencing turnover intention (explanatory power: 21.0%).ConclusionStrategies or interventions relieving job stress and strengthening professional self-concept could decrease turnover intention. Age and educational level need to be considered when developing and implementing interventions. These results were similar to the results of studies on the turnover intention of hospital nurses. However, the results of this study are meaningful in the reality that there is a great lack of research on the turnover intention of nurses working at dementia care centers in community.